Occult Osteochondral Injuries in Athletes: Advanced Imaging, Clinical Evolution, and Criteria for Safe Return to Sport - Jose Gregorio Requena Rodriguez; Loys Eliana Tello Caldas; Edunice Beatriz Mora López; Juan Pablo Monroy Moreno; Angie Michelle Junco Aguaiza; Juan José Dorado Victoria; Fabián Patricio Miranda Yáñez; Jorge Roberto Gandarilla San Luis; Nicolás Camilo Rivera Calvo; Eduardo Andres Castillo González (IECCMEXICO, 2026)
Occult osteochondral lesions represent an important challenge in sports medicine because they may remain undetected during initial assessment despite persistent pain, swelling, mechanical symptoms, and functional limitation. This study analyzed the role of diagnostic imaging, clinical and structural evolution, and return-to-sport criteria in athletes with osteochondral injuries, with particular emphasis on the knee and ankle. An integrative descriptive and analytical review was conducted using the Scientific Method, incorporating evidence related to magnetic resonance imaging, computed tomography, CT arthrography, conservative management, surgical treatment, rehabilitation, and athletic recovery. The findings demonstrated that conventional radiography has limited sensitivity for early osteochondral abnormalities, whereas magnetic resonance imaging provides superior visualization of cartilage integrity, bone marrow edema, subchondral changes, and lesion stability. Computed tomography and CT arthrography offer complementary value for defining osseous architecture and selected cartilage-surface abnormalities. Clinical improvement and radiological recovery were not consistently parallel, indicating that symptomatic improvement does not necessarily imply complete structural restoration. Surgical procedures such as bone marrow stimulation, fixation, osteochondral transplantation, and cartilage restoration showed favorable clinical and return-to-sport outcomes in appropriately selected patients, although return to the pre-injury level was consistently lower than return to sport at any level. The reviewed literature also revealed substantial heterogeneity in rehabilitation protocols and a predominant reliance on time-based criteria for sports clearance. Overall, the evidence supports an individualized and multidimensional return-to-sport approach integrating symptoms, range of motion, muscle strength, neuromuscular control, tolerance to loading, sport-specific performance, psychological readiness, and imaging follow-up when clinically indicated. Early diagnosis and criterion-based rehabilitation may contribute to safer athletic reintegration and improved long-term preservation of joint function.